High Mobility Group Box 1 Promotes Aortic Calcification in Chronic Kidney Disease via the Wnt/β-Catenin Pathway - Jin, Xiucai; Rong, Shu; Yuan, Weijie; Gu, Lijie; Jia, Jieshuang; Wang, Ling; Yu, Honglei; Zhuge, Yifeng (Frontiers in Physiology, 2018)
Vascular calcification (VC) is common in chronic kidney disease (CKD), where cardiovascular mortality remains the leading cause of death. Here, we examined the role of high-mobility group box1 (HMGB1), a nuclear DNA-binding protein involved in inflammation, in aortic calcification and renal dysfunction induced by high phosphate in a mouse model of CKD induced by 5/6 nephrectomy. HMGB1 and kidney function markers were measured by ELISA in the serum of CKD patients and in CKD mice. Sections of the aortas of mice were analyzed by immunofluorescence and Alizarin red staining, and protein lysates were generated to analyze the expression of related proteins in response to silencing of HMGB1 or β-catenin by western blotting. Our results showed that serum HMGB1 levels were significantly higher in CKD patients than in healthy controls and related to disease stage. High phosphate promoted the translocation of HMGB1 from the nucleus to the cytosol and aortic calcification in CKD mice in vivo, whereas HMGB1 knockdown ameliorated renal and vascular function. β-catenin silencing reversed high phosphate-induced calcification and restored renal marker levels. Taken together, our results suggest that HMGB1 is involved in VC associated with CKD via a mechanism involving the β-catenin.